2010
DOI: 10.1111/j.1475-097x.2009.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating GFR in children with 99mTc‐DTPA renography: a comparison with single‐sample 51Cr‐EDTA clearance

Abstract: Glomerular filtration rate (GFR) measurement by (51)Cr-ethylenediaminetetraacetic acid (EDTA) and blood sampling in children is usually cumbersome for the patient, parents and laboratory technicians. We have previously developed a method accurately estimating GFR in adults. The aim of the present study was to evaluate the accuracy of this non-invasive method in children. We calculated GFR from (99m)Tc-diethylene triamine pentaacetic acid (DTPA) renography and compared with (51)Cr-EDTA plasma clearance of 29 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Although the norms reported in the literature are for 51 Cr-EDTA-GFR, the correlation between 99m Tc-DTPA and 51 Cr-EDTA plasma clearances is excellent. DTPA may give slightly higher values than EDTA (<5% difference), but this difference is not clinically significant [21, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the norms reported in the literature are for 51 Cr-EDTA-GFR, the correlation between 99m Tc-DTPA and 51 Cr-EDTA plasma clearances is excellent. DTPA may give slightly higher values than EDTA (<5% difference), but this difference is not clinically significant [21, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…The correlation between 99m Tc‐DTPA renography and 51 Cr‐EDTA plasma CL was for all children R = 0.96 (n = 29; P < .0001), for children >2 years of age R = 0.96 (n = 18; P < .0001) and for children <2 years R = 0.84 (n = 11; P < .001). The authors concluded that the assessment of GFR from 99m Tc‐DTPA renography is reliable and comparable to GFR calculated from 51 Cr‐EDTA plasma CL and, given that it is less invasive, may be preferable in the pediatric population …”
Section: Markers For Renal Function Assessmentmentioning
confidence: 95%
“…The authors concluded that the assessment of GFR from 99m Tc-DTPA renography is reliable and comparable to GFR calculated from 51 Cr-EDTA plasma CL and, given that it is less invasive, may be preferable in the pediatric population. 34…”
Section: S13mentioning
confidence: 99%
“…24 The patients in the present study represented all five stages of renal disease, according to K/DOQI guidelines 12 and, because 59% of them were in CKD stages 1 -2 and had raised GFR levels, the GFR was underestimated by all four equations. This underestimation was consistent with previous reports for the MDRD equations.…”
Section: 11mentioning
confidence: 99%